Dinamika Internalisasi Hukum Islam Kedalam Peraturan Perundang-Undangan Di Indonesia - Hendra Irawan (Istinbath : Jurnal Hukum, 2021)
Islamic law in Indonesia is law based on the Qur'an and al-Sunnah, and developed through ijtihad in the context of plural Indonesian society. Although Islam is not a state religion, Islam can sublimate through the legal order (fiqh and shari'ah) which is pervasive in the behavior of the Indonesian nation. This paper aims to examine the dynamics of the internalization of Islamic law into the normative regulatory system in Indonesia. This article was written using a normative legal research method, with a historical and conceptual approach. Data obtained from secondary data sources in the form of secondary and tertiary legal materials, which were analyzed qualitatively. The results of the study show that Islamic law has been in effect since the beginning of the entry of Islam in Indonesia. Even in subsequent developments, Islamic law became one of the three basic ingredients of national law, in addition to customary law and western law. During the Old Order and the New Order, Islamic law was not fully accommodated in the Outlines of State Policy. However, in the reform era, Islamic law was only accommodated in national law. This shows that the dynamics of the internalization of Islamic law into the legal system is influenced by historical and political factors.